When discourse met null subjects - Jimenez-Fernandez, Angel (Borealis – An International Journal of Hispanic Linguistics, 2016)
In this paper a novel view of the distribution of null subjects in Spanish is explored in which the discourse category which the antecedent of pro is analysed. Implementing Frascarelli’s (2007) work, I propose that the crucial condition to meet is for the null subject to be coreferential with an Aboutness-Shift Topic, which must be either an explicit or null copy in the local domain where pro is inserted. When null, this antecedent can refer back to any type of discourse category. The analysis is supported by an experiment run among native speakers of Spanish.